THE EFFECT OF WORK SATISFACTION ON EMPLOYEE LOYALTY IN SMK YASBU AL QOMARIYAH SODONGHILIR TASIKMALAYA DISTRICT - Kusuma Agdhi Rahwana; Suci Putri Lestari (JOBS (Jurnal Of Business Studies), 2019)
The purpose of this study was to determine the effect of job satisfaction on employee loyalty at the Bina Umat Foundation (YASBU) Al-qomariyah Vocational School at Sodonghilir. The research method used in this research is explanatory research. The use of this method is because the researcher does not only describe empirical facts found in the field, but also intends to analyze and explain the influence between variables. Data collection is obtained through interviews, questionnaires and literature studies. The population in this study were employees of the YASBU Al-qomariah Vocational School.Methods Analysis of the data used is the Multiple Regression Analysis, where data is processed with the help of SPSS. The results of testing the data using the regression equation show the results of the existence of a positive and significant influence variable satisfaction with loyalty. This means that the higher the job satisfaction of an employee, the higher the loyalty of employees of YASBU Al-qomariah Vocational School